ARTIFICIAL INTELLIGENCE-ASSISTED COUNSELING AND ITS IMPACT ON PSYCHOLOGICAL WELL-BEING AMONG UNIVERSITY STUDENTS: THE MEDIATING ROLE OF ACADEMIC RESILIENCE - Zulkarnain; Fitri Yuniarti; Asmarita; Zulhamdan; Izzah Munisah Farhati (PT. Cadas Insan Madani, 2026)
Artificial intelligence has increasingly become an integral part of digital mental health services, offering innovative approaches to counseling and psychological support in higher education. AI-assisted counseling platforms enable university students to access immediate guidance, emotional support, and self-reflection resources regardless of time and location. Despite their growing adoption, limited research has explored how students perceive and experience these technologies in relation to their psychological well-being. This study aims to explore the lived experiences of university students who have utilized AI-assisted counseling for psychological well-being through a phenomenological approach. The study involved 12 undergraduate students from diverse academic disciplines who had used AI-based counseling applications or conversational AI for academic and emotional support for at least three months. Data were collected through in-depth semi-structured interviews and reflective field notes. The data were analyzed using Interpretative Phenomenological Analysis (IPA), including iterative coding, theme development, and interpretative synthesis. Four major themes emerged: (1) accessibility and immediacy as primary advantages of AI-assisted counseling, (2) emotional comfort through non-judgmental interactions, (3) perceived limitations in empathy and human connection, and (4) AI as a complementary rather than a substitute for professional counselors. Participants reported that AI-assisted counseling encouraged self-reflection, emotional regulation, and academic resilience while emphasizing the continued importance of professional counselors in addressing complex psychological concerns. The findings suggest that AI-assisted counseling can serve as a valuable complementary resource for promoting psychological well-being among university students when implemented alongside ethical standards and human-centered counseling practices. This study contributes to the growing literature on digital mental health by providing insights into students' lived experiences and offering practical implications for the future development of AI-supported counseling services in higher education.